#TITLE_ALTERNATIVE# - PRAMESWARI (NIM 17502009), INTAN
Breast cancer is one of the types of cancers that attack most women. It also has been the second caused of women's death after cervix cancer. The possibility to heal for breast cancer reaches 100% if it detected early. That's why medical check up routines takes important part, especially to some people who in the state of high risk to the cancer. However facilities to detect breast cancer still in minor stakes and only be found in big hospitals, this has caused the only people who can access it are people who live in big cities with big fund. This is the reason that in Indonesia this cancer detected in advanced stage. To solve this problem, electrical impedance tomography technology can be an alternative solving. This is related due the minimum amount of money that will be used, and operating system that user friendly so can be used by everyone.